Obesity and Risk of Colorectal Adenomatous Polyps: a Case-Control Study in Hospital Kuala Lumpur - Ramadas, Amutha; Hambali, Zarida; Alif Gul, Yunus Gul; Jabal, Mohd Faizal; Kandiah, Marlini (Nutrition Society of Malaysia, 2009)

(untitled)
Colorectal adenomas are precursor lesions of colorectal cancer. Several studies have proposed that obesity is a risk factor for colorectal adenoma. This case-control study examined the relationship between body mass index (BMI), waist circumference, waistto-hip ratio (WHR), body fat percentage and colorectal adenomatous polyps (CRA) in patients who have had a colonoscopy at the Hospital Kuala Lumpur (HKL). Fifty-nine patients (42 males and 17 females) positively identified as having CRA and 59 polypfree subjects were recruited as controls (33 males and 26 females). A pre-tested questionnaire was used to collect socio-economic information, while anthropometric measurements were determined directly by established methods. The mean BMI of female case subjects was significantly higher than control females (25.63 + 4.87 kg/m2 vs. 23.86 + 3.70 kg/m2, p<0.05) but the difference in BMI was not significant in men. The mean WHR of male subjects was significantly higher in the case group (0.92 + 0.07 vs. 0.90 + 0.06, p<0.05). After adjusting for confounders, waist circumference was the only indicator that was found to significantly increase the risk for CRA in women (OR = 6.349, 95% CI = 1.063 37.919). Higher BMI, WHR and body fat percentage showed a non-significant risk in female subjects. In men, none of the obesity indicators were found to be significant risk factors for CRA. These findings suggest that abdominal obesity may be a contributing factor to CRA risk particularly in women. A prospective study is needed to confirm the role of obesity in the development of CRA in Malaysians.